(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article explores the fundamental concepts of syntax, examining both traditional and cognitive approaches. Syntax, the study of sentence structure, plays a crucial role in linguistics. Traditional approaches focus on formal rules and structures, while cognitive approaches delve into the mental processes underlying language production. The article discusses key units in syntax and illustrates how each approach contributes to our understanding of language structure.